Sulforaphane‐induced apoptosis in Xuanwei lung adenocarcinoma cell line XWLC‐05. Issue 1 (23rd November 2016) - Zhou, Lan; Yao, Qian; Li, Yan; Huang, Yun‐chao; Jiang, Hua; Wang, Chuan‐qiong; Fan, Lei
Abstract : Background: Xuanwei district in Yunnan Province has the highest incidence of lung cancer in China, especially among non‐smoking women. Cruciferous vegetables can reduce lung cancer risk by prompting a protective mechanism against respiratory tract inflammation caused by air pollution, and are rich in sulforaphane, which can induce changes in gene expression. We investigated the effect of sulforaphane‐induced apoptosis in Xuanwei lung adenocarcinoma cell line (XWCL‐05) to explore the value of sulforaphane in lung cancer prevention and treatment. Methods: Cell growth inhibition was determined by methyl thiazolyl tetrazolium assay; cell morphology and apoptosis were observed under transmission electron microscope; cell cycle and apoptosis rates were detected using flow cytometry; B‐cell lymphoma 2 (Bcl‐2) and Bcl‐2‐like protein 4 (Bax) messenger RNA expression were determined by quantitative PCR; and p53, p73, p53 upregulated modulator of apoptosis (PUMA), Bax, Bcl‐2, and caspase‐9 protein expression were detected by Western blotting. Results: Sulforaphane inhibited XWLC‐05 cell growth with inhibitory concentration (IC)50 of 4.04, 3.38, and 3.02 μg/mL at 24, 48, and 72 hours, respectively. Sulforaphane affected the XWLC‐05 cell cycle as cells accumulated in the G2/M phase. The proportion of apoptotic cells observed was 27.6%. Compared with the control, the sulforaphane group showed decreased Bcl‐2 and p53 expression, and significantly increased p73, PUMA, Bax, and caspase‐9 protein expression ( P  < 0.05). Conclusion: Sulforaphane induces Xuanwei lung adenocarcinoma cell apoptosis. Its possible mechanism may involve the upregulation of p73 expression and its effector target genes PUMA and Bax in lung cancer cells, downregulation of the anti‐apoptotic gene B cl ‐2, and activation of caspase‐9. It may also involve downregulation of the mutant p53 protein.